Enhancing the rheological properties and shale inhibition behavior of water-based mud using nanosilica, multi-walled carbon nanotube, and graphene nanoplatelet - A. Aftab; A.R. Ismail; Z.H. Ibupoto (Egyptian Journal of Petroleum)
Five different drilling mud systems namely potassium chloride (KCl) as a basic mud, KCl/partial hydrolytic polyacrylamide (PHPA), KCl/graphene nanoplatelet (GNP), KCl/nanosilica and KCl/multi-walled carbon nano tube (MWCNT) were prepared and investigated for enhancement of rheological properties and shale inhibition. Nanoparticles were characterized in drilling mud using transmission electron microscope (TEM) analysis. Mineralogical analysis of shale was examined by X-ray diffraction (XRD). Five shale plugs were prepared using compactor cell for the determination of shale swelling. Shale swelling was determined using the linear swell meter (LSM) for 20 hours. Results revealed that basic mud and KCl/polymer mud systems shows 30% and 24% change in shale volume. MWCNT, nanosilica and GNP were added separately in the KCl mud system. 0.1 ppb of each MWCNT and nanosilica showed 32% and 33% change in shale volume. However, when the shale was interacted with WBM containing 0.1 ppb of GNP, it was found that only 10% change in shale volume occurred. The results showed that the addition of nanoparticles in the KCl mud system improved the shale inhibition. API, HPHT filtrate loss volume, plastic viscosity (PV) and yield point (YP) were improved using GNP. It is learned from the experimental work that small concentration of KCl with GNP can mitigate shale swelling compared to the mud contains higher concentration of KCl and PHPA in WBM. Thus, GNP can be a better choice for enhancement of WBM performance.